Pengaruh Motivasi Belajar Dan Status Ekonomi Orang Tua Terhadap Minat Studi Lanjut Siswa/Siswi Sma Dan Smk Di Bogor Pada Bidang Ekonomi Dan Manajemen - Muktiadji, Nusa; Gendalasari, Gen Gen; Sudradjat, Sudrajat; Hendrian, Ganjar (LPPM Institut Bisnis dan Informatika Kesatuan, 2016)
The interest to continue study to higher education in high school students is formed by many factors. To name a few, first is the motivation to study, and the second is the parents’ social economy condition. The students with higher motivation are suspected to have bigger chance to continue study compared to students with lower motivation to study. This also works for the parents’ state of social economy. The research is conducted with 1.024 respondents of high school students in Bogor. To learn the influence of motivation and parents’ state of social economy in continuing study to higher education, logistic regression is used as research analysis method. The results show that motivation to study has significant influence on high school students’ interest to continue their study in Bogor. Formal education and parents’ average income do not influence the shaping of interest to continue study. The faculty of economy and management are discovered as most wanted program by high school students in Bogor.